Manajemen Sarana Prasarana Di RA Rahmah El Yunusiyyah Padang Panjang - Wahyuni, intan S (JURNAL TILA ( Tarbiyah Islamiyah Lil Athfaal ), 2021)
ABSTRACT To support the learning process based on the curriculum that has been included, the founding foundation of PAUD must meet the minimum standards of infrastructure that have been determined. RA Rahmah El Yunusiyyah is an early childhood education institution that has good and adequate learning facilities and infrastructure. The purpose of this study is to describe the procurement, inventory, use, maintenance, accountability, destruction of infrastructure. This study uses a descriptive method with a qualitative approach. The sample of this research is the infrastructure in RA Rahmah El Yunusiyyah, Padang Panjang. The results of data analysis showed that planning, procurement, inventory, use, maintenance, accountability, destruction were carried out by the head of the RA and based on the direction of the leadership as well as the Rahmah El Yunusiyyah Foundation, Padang Panjang.